1993
DOI: 10.4319/lo.1993.38.4.0879
|View full text |Cite
|
Sign up to set email alerts
|

Food‐web responses to species invasion by a predatory invertebrate: Bythotrephes in Lake Michigan

Abstract: Several developments in the offshore plankton community accompanied the invasion of Bythotrephes cederstroemi Schoedler (Crustacea: Cladocera: Cercopagidae) into Lake Michigan. A native predatory cladoceran, Leptodora kindti, became significantly reduced in abundance and biomass in the presence of Bythotrephes. The offshore Daphnia assemblage, which had consisted of three species before the arrival of Bythotrephes, was reduced to dominance by only D. galeata mendotae. Abundances of Daphnia species exhibited re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
153
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 30 publications
11
153
2
Order By: Relevance
“…They hypothesized that this was due to either predator avoidance behavior, or localized depletion. Further, Lehman and Caceres (1993) showed that the cladocerans Bosmina longirostris, D. mendotae, and D. pulicaria shifted their vertical distributions following the invasion of Bythotrephes longimanus in Lake Michigan offshore from Grand Haven, Michigan. Similarly, Johannsson (O. Johannsson, Department of Fisheries and Oceans Canada, 3 Mar 04) has found that the average depth of Bosmina and Dapnia in Lake Erie is inversely related to Bythotrephes densities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They hypothesized that this was due to either predator avoidance behavior, or localized depletion. Further, Lehman and Caceres (1993) showed that the cladocerans Bosmina longirostris, D. mendotae, and D. pulicaria shifted their vertical distributions following the invasion of Bythotrephes longimanus in Lake Michigan offshore from Grand Haven, Michigan. Similarly, Johannsson (O. Johannsson, Department of Fisheries and Oceans Canada, 3 Mar 04) has found that the average depth of Bosmina and Dapnia in Lake Erie is inversely related to Bythotrephes densities.…”
Section: Discussionmentioning
confidence: 99%
“…One factor that could influence an adaptive response of Lake Michigan D. mendotae to Mysis is the recent invasion of Bythotrephes (Lehman 1987). Bythotrephes is a visual predator, and therefore it may be adaptive for D. mendotae to respond to Bythotrephes by swimming lower in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…Early on, the long tail spine was demonstrated to protect Bythotrephes from small young of the year (YOY) fish (Barnhisel 1991a, b;Barnhisel and Harvey 1995), although bigger fish could ingest large numbers of adults (Keilty 1988;Mills et al 1992;Branstrator and Lehman 1996). The spiny water flea was shown to be epilimnetic with mid-summer density oscillations (Berg and Garton 1988;Lehman 1991;Lehman and Cáceres 1993), to have high energetic demands (Lehman and Cáceres 1993;Yurista et al 2010), and to depress herbivorous cladocerans such as Daphnia mendotae, D. retrocurva, and Bosmina (Lehman and Cáceres 1993;Schulz and Yurista 1999;Barbiero and Tuchman 2004). Bythotrephes' diets were examined from stomach contents (Lehman and Branstrator 1995;Schulz and Yurista 1995), and diapausing eggs were quantified and hatched (Yurista 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, specific theoretical models, allied with new field data, will be required to clarify the role of invasion in establishing the periodic travelling waves in E. autumnata. In addition, we are aware of two examples of field data demonstrating spatio-temporal oscillations behind ecological invasions: the invasion of Daphnia by its crustacean predator Bythotrephes in Lake Michigan (Lehman & Caceres 1993), and the invasion of thistle populations by tephritid flies Urophora carudi (Jeltsch et al 1992). However, neither dataset has been analysed for periodic travelling wave behaviour in the manner described in §2.…”
mentioning
confidence: 99%